دراسة تحليلية للطلب الفعال كوظائف رئيسة للنقود في الاقتصاد الاسلامي (المجلة العراقية للعلوم الاقتصادية, 2018)
A study of money effective demand's major functions in Islamic economy as means for exchange and a measurement of value and accumulation (saving) as a financial reserve and their application in the modern financial system in order to serve society. Research hypothesis:Money in Islamic economy has major functions upon which effective demand is based. Importance of research:It's represented by the organization of economic life in general and society members in particular through the money major functions as effective demand. Research plan:Section-1-: the function of money as a mean for exchange (transactions) effective demand.Section -2-: function of money a measurement of value (a calculation mean) and for accumulation (saving) – cash reserve-